N6-Methyladenosine modification: a novel pharmacological target for anti-cancer drug development - Yi Niu; Arabella Wan; Ziyou Lin; Xiongbin Lu; Guohui Wan (Elsevier, 2018)
N6-Methyladenosine (m6A) modification is the most pervasive modification of human mRNA molecules. It is reversible via regulation of m6A modification methyltransferase, demethylase and proteins that preferentially recognize m6A modification as "writers", "erasers" and "readers", respectively. Altered expression levels of the m6A modification key regulators substantially affect their function, leading to significant phenotype changes in the cell and organism. Recent studies have proved that the m6A modification plays significant roles in regulation of metabolism, stem cell self-renewal, and metastasis in a variety of human cancers. In this review, we describe the potential roles of m6A modification in human cancers and summarize their underlying molecular mechanisms. Moreover, we will highlight potential therapeutic approaches by targeting the key m6A modification regulators for cancer drug development. Key words: N6-Methyladenosine, Human cancer, Pharmacological target, m6A modification regulator, Drug development